The ALDH21 gene found in lower plants and some vascular plants codes for a NADP+ -dependent succinic semialdehyde dehydrogenase - Kopečná, Martina; Vigouroux, Armelle; Vilím, Jan; Končitíková, Radka; Briozzo, Pierre; Hájková, Eva; Jašková, Lenka; von Schwartzenberg, Klaus; Šebela, Marek; Moréra, Solange; Kopečný, David (The Plant journal, 2017)
Lower plant species including some green algae, non-vascular plants (bryophytes) as well as the oldest vascular plants (lycopods) and ferns (monilophytes) possess a unique aldehyde dehydrogenase (ALDH) gene named ALDH21, which is upregulated during dehydration. However, the gene is absent in flowering plants. Here, we show that ALDH21 from the moss Physcomitrella patens codes for a tetrameric NADP+ -dependent succinic semialdehyde dehydrogenase (SSALDH), which converts succinic semialdehyde, an intermediate of the γ-aminobutyric acid (GABA) shunt pathway, into succinate in the cytosol. NAD+ is a very poor coenzyme for ALDH21 unlike for mitochondrial SSALDHs (ALDH5), which are the closest related ALDH members. Structural comparison between the apoform and the coenzyme complex reveal that NADP+ binding induces a conformational change of the loop carrying Arg-228, which seals the NADP+ in the coenzyme cavity via its 2'-phosphate and α-phosphate groups. The crystal structure with the bound product succinate shows that its carboxylate group establishes salt bridges with both Arg-121 and Arg-457, and a hydrogen bond with Tyr-296. While both arginine residues are pre-formed for substrate/product binding, Tyr-296 moves by more than 1 Å. Both R121A and R457A variants are almost inactive, demonstrating a key role of each arginine in catalysis. Our study implies that bryophytes but presumably also some green algae, lycopods and ferns, which carry both ALDH21 and ALDH5 genes, can oxidize SSAL to succinate in both cytosol and mitochondria, indicating a more diverse GABA shunt pathway compared with higher plants carrying only the mitochondrial ALDH5.
Keywords: aldehyde dehydrogenase; kyselina jantarová; Ferns; Phylogeny; Substrate Specificity; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; ALDH5; Protein Conformation; Succinic Acid; ALDH21; succinic semialdehyde; kapradiny; Succinate-Semialdehyde Dehydrogenase; sukcinátsemialdehyddehydrogenasa; structure-function; Physcomitrella patens; rostlinné geny; Genes, Plant; Bryophyta; substrátová specifita; fylogeneze; site-directed mutagenesis; gamma-Aminobutyric Acid; GABA; γ-aminobutyric acid; X-ray crystallography; konformace proteinů